2013
DOI: 10.1371/journal.pone.0076699
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GSK3β by Sirt2 Is Required for Early Lineage Commitment of Mouse Embryonic Stem Cell

Abstract: Sirt2, a member of the NAD+-dependent protein deacetylase family, is increasingly recognized as a critical regulator of the cell cycle, cellular necrosis and cytoskeleton organization. However, its role in embryonic stem cells (ESCs) remains unclear. Here we demonstrate that Sirt2 is up-regulated during RA (retinoic acid)-induced and embryoid body (EB) differentiation of mouse ESCs. Using lentivirus-mediated shRNA methods, we found that knockdown of Sirt2 compromises the differentiation of mouse ESCs into ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…1h,i). Our results are in agreement with previous studies showing downregulation of SIRT1 during hESC differentiation 29,30 and upregulation of SIRT2 during mouse ESC differentiation 31 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1h,i). Our results are in agreement with previous studies showing downregulation of SIRT1 during hESC differentiation 29,30 and upregulation of SIRT2 during mouse ESC differentiation 31 .…”
Section: Resultssupporting
confidence: 94%
“…In agreement with our results, previous studies showed upregulation of SIRT1 in hPSCs 29,30 and SIRT1’s important roles for generation of mouse iPSCs 30,37 . In addition, the study by Si et al 31 showed that SIRT2 is upregulated during in vitro differentiation of mouse ESCs and SIRT2KD promotes mesoderm and endoderm lineages while compromising ectoderm differentiation. In contrast, our results show that SIRT2 regulates more fundamental stem cell functions such as metabolism, cell survival/death, and pluripotent differentiation potential in hPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that members of the sirtuin (Sirt) family of deacetylases regulate GSK3. Sirt2 activity is associated with inhibition of GSK3 (Dan et al, 2012; Si et al, 2013), whereas Sirt1 has been reported to either activate (Monteserin-Garcia et al, 2013) or inhibit (Li et al, 2013) GSK3. GSK3 also modulates post-translational modifications of histones by regulating several histone acetyltransferases (HATs).…”
Section: Regulation Of Gsk3-mediated Substrate Phosphorylationmentioning
confidence: 99%
“…Although glycolytic flux is common across all stages of pluripotency, the relative contributions of glycolysis versus OxPhos do vary. The primed pluripotent state of hPSCs and mEpiSCs is almost exclusively glycolytic (Tesar et al, 2007;Nichols and Smith, 2009;Takashima et al, 2014;Theunissen et al, 2014), whereas naïve hPSCs and mESCs utilize a bivalent metabolic system with a greater reliance on oxidative metabolism (Lee et al, 2012;Zhou et al, 2012;Si et al, 2013;Mu et al, 2015;Cha et al, 2017). Indeed, early preparatory phase glycolytic metabolites such as fructose 1, 6-bisphosphate are enriched in primed PSCs without accumulation of downstream metabolites, suggesting that these glycolytic intermediates may be consumed for anabolism or one-carbon metabolism (Tesar et al, 2007;Zhou et al, 2012;Gafni et al, 2013;Takashima et al, 2014;Sperber et al, 2015).…”
Section: Pluripotent Stem Cell Metabolism Glycolysismentioning
confidence: 99%